Development of a novel integrated model GOTRESS+ for predictions and assessment of JT-60SA operation scenarios including the pedestal. (4th October 2021) - Honda, M.; Aiba, N.; Seto, H.; Narita, E.; Hayashi, N.
Abstract: A novel integrated model GOTRESS+ has been developed, which consists of the iterative transport solver GOTRESS as a kernel of the integrated model, the equilibrium and current profile alignment code ACCOME and the neutral beam heating/current-drive code OFMC. GOTRESS is able to robustly find out an exact solution of the stationary-state transport equations even with a stiff turbulent transport model, taking advantage of global optimization techniques such as a genetic algorithm. GOTRESS+ is then suitable for self-consistently assessing the stationary-state plasma performance of JT-60SA as well as ITER and DEMO or validating their feasibility. Recently GOTRESS+ has been extended to incorporate the in-house EPED1 model exploiting the MHD stability code MARG2D and is now able to predict the plasma profiles even with the pedestal over the entire region from the magnetic axis to the plasma boundary in a self-consistent manner. The two JT-60SA operation scenarios including the ITER-like inductive scenario and the high β fully non-inductively current driven scenario have been assessed by GOTRESS+ with the CDBM turbulent transport model and then were found to be feasible with most of the target dimensionless parameters met.